Transcendental Poetry in the Baroque Period: Angelus Silesius’s Religious and Philosophical Epigrams as Reflections About the Self and the Divine - Classen, Albrecht (Cultural Arts Research and Development, 2025)
One of the greatest poets of epigrams, Angelus Silesius, was not only highly famous for his short stanzas written in the latter half of the seventeenth century. He also exerted, both during his lifetime and then during his posterity, and thus until today, a deep influence on poetry, philosophy, and theology. But his epigrams are extremely difficult to understand and represent, despite their formal simplicity, a major intellectual challenge. This is both a hurdle and simultaneously an opportunity because human epistemology grows when there are barriers, especially linguistic, conceptual, and intellectual ones, under the right circumstances. This paper will reintroduce Silesius as a Baroque poet who deserves our full attention today because he provided us in a most unique fashion with literary images to capture some of the most subtle, spiritual, and sensory experiences in human life formulated during the Baroque period. Relying on dialectics, rhetorical strategies, and metaphorical language, Silesius proves to be one of the most meaningful poets from the past who speaks to us today and probably also tomorrow, offering perspectives toward the personal experience of the transcendental.